Reflections of Positive Experiences in Midwifery and Nursing of Maternal-Newborn Education in Thailand: Lessons Learned from Naresuan University - Pantipa Buakhai; Pratuma Rithpho (San Beda University, 2019)
The success of maternal and child health practices emphasizes on health policies, building effective partnerships, advocating for investments in maternal and newborn health, and coordinating research that focuses on improving maternal health in pregnancy and during and after childbirth.  In these situations, nurses and midwives are the key resources that comprise the greater part of the health-care workforce. Nurses and midwives make substantial contributions to healthcare delivery systems especially in primary care, acute care, and community care setting. Thailand has an excellent production of nurses since they can perform duties as a nurse and as a midwife. This is what we think nurses from other countries should apply in their countries to improve health services. We can also show that our country has a low gender gap in employment not just in nursing. This paper would like to present the lessons learned from Thailand Nursing Education purposed in midwifery, maternal, and newborn nursing at Naresuan University. Specifically, the purpose of this article was to discuss the midwife and maternal and newborn education standards in Thailand and describe the experiences using reflective knowledge in order to inform current and future midwifery and maternal and newborn nursing practices in Thailand.